PENGATURAN DESA DALAM PERSPEKTIF LAW AS AN ALLOCATIVE SYSTEM - sofyanoor, andin (Lampung University, 2014)
Writing this article aims to provide an assessment of the academic village setting contained in Law No. 6 of 2014 is based on a legal approach as the allocation system. Based on normative pendekaran, concluded that that the village setting in the Village Act 2014 has met the academic aspects referred Friedman approach to the law as a system of allocation. However, to achieve a prosperous village inhabitants, it is recommended 1) the general policy of the development of village autonomy as one more attempt to direct and optimize the implementation of rural development in a comprehensive, integrated, and coordinated in order to achieve the goals effectively and efficiently; 2) the development of village autonomy is directed at creating a mission closer to the peoples welfare and development services for the community; and 3) development of village autonomy necessary synergy between the various sectors and levels of authority in governance, in particular districts as local work unit closest to the village.Â Keywords: Village, Decentralization, and Legal System Allocation